Research progress on the pharmacological effects of berberine targeting mitochondria - Fang, Xinyi; Wu, Haoran; Wei, Jiahua; Miao, Runyu; Zhang, Yanjiao; Tian, Jiaxing (Frontiers in Endocrinology, 2022)
Berberine is a natural active ingredient extracted from the rhizome of Rhizoma Coptidis, which interacts with multiple intracellular targets and exhibits a wide range of pharmacological activities. Previous studies have preliminarily confirmed that the regulation of mitochondrial activity is related to various pharmacological actions of berberine, such as regulating blood sugar and lipid and inhibiting tumor progression. However, the mechanism of berberine's regulation of mitochondrial activity remains to be further studied. This paper summarizes the molecular mechanism of the mitochondrial quality control system and briefly reviews the targets of berberine in regulating mitochondrial activity. It is proposed that berberine mainly regulates glycolipid metabolism by regulating mitochondrial respiratory chain function, promotes tumor cell apoptosis by regulating mitochondrial apoptosis pathway, and protects cardiac function by promoting mitophagy to alleviate mitochondrial dysfunction. It reveals the mechanism of berberine's pharmacological effects from the perspective of mitochondria and provides a scientific basis for the application of berberine in the clinical treatment of diseases.